Energy efficient direct transesterification of Nannochloropsis sp. using hydrodynamic cavitation - Nirmalasari, Jiran; Setyawan, Martomo; Jamilatun, Siti; Pitoyo, Joko; Hakika, Dhias Cahya (Institute of Advanced Engineering and Science, 2025)
The increasingly limited supply of fossil fuels requires renewable fuel as an alternative source. Nannochloropsis sp. is a microalgae species containing a lipid content of between 12 and 53%, which can be converted to biofuel as an alternative source of fossil fuels through a transesterification process. Up to this date, the literature has reported no studies on biodiesel production from Nannochloropsis sp. via direct transesterification with catalyst using hydrodynamic cavitation. The direct transesterification process introduced 7.5 g of microalgae, 40 ml of methanol, 90 ml of hexane, and 0.0225 g of sodium hydroxide into the sample chamber. These mixtures were passed within the cavitation using a pressure driver and transformed into fatty acid methyl ester (FAME). The catalytic hydrodynamic cavitation method produces a higher extract yield than the stirring one. Regarding the FAME composition, the catalytic hydrodynamic cavitation method is dominated by saturated fatty acid (palmitic), while the stirring catalytic method is dominated by monounsaturated fatty acid (oleic). The hydrodynamic cavitation method provides a lower average degree of unsaturation and shorter chain length than the stirring catalytic method.